Balanced Caloric Restriction Minimizes Changes Caused by Aging on the Colonic Myenteric Plexus - Mari, Renata de Britto [UNESP]; Stabille, Sandra Regina; de Faria, Haroldo Garcia; Pereira, Joice Naiara Bertaglia; Guimarães, Juliana Plácido; Marinsek, Gabriela Pustiglione [UNESP]; de Souza, Romeu Rodrigues (Taylor & Francis, 2018)
Aging can promote significant morphofunctional changes in the gastrointestinal tract (GIT). Regulation of GIT motility is mainly controlled by the myenteric neurons of the enteric nervous system. Actions that aim at decreasing the aging effects in the GIT include those related to diet, with caloric restriction (CR). The CR is achieved by controlling the amount of food or by manipulating the components of the diet. Therefore, the objective of this study was to evaluate different levels of CR on the plasticity of nicotinamide adenine dinucleotide phosphate– (NADPH-) reactive myenteric neurons in the colon of Wistar rats during the aging process using ultrastructural (transmission electron microscopy) and morphoquantitative analysis. Wistar male rats (Rattus norvegicus) were distributed into 4 groups (n = 10/group): C, 6-month-old animals; SR, 18-month-old animals fed a normal diet; CRI, 18-month-old animals fed a 12% CR diet; CRII, 18-month-old animals fed a 31% CR diet. At 6 months of age, animals were transferred to the laboratory animal facility, where they remained until 18 months of age. Animals of the CRI and CRII groups were submitted to CR for 6 months. In the ultrastructural analysis, a disorganization of the periganglionar matrix with the aging was observed, and this characteristic was not observed in the animals that received hypocaloric diet. It was observed that the restriction of 12.5% and 31% of calories in the diet minimized the increase in density and cell profile of the reactive NADPH neurons, increased with age. This type of diet may be adapted against gastrointestinal disturbances that commonly affect aging individuals.
Keywords: aging; enteric nervous system; food restriction; nitric oxide